2007
DOI: 10.1016/j.amjhyper.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled Endothelial Nitric Oxide Synthase and Oxidative Stress in a Rat Model of Pregnancy-Induced Hypertension

Abstract: These data suggest that increased superoxide production by NADPH oxidase, peroxynitrite degradation of BH4, and uncoupled eNOS contribute to endothelial dysfunction in a rat model of pregnancy-induced hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
47
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 31 publications
9
47
0
3
Order By: Relevance
“…Clinically, recombinant IL-10 has been used with moderate success for the treatment of psoriasis and rheumatoid arthritis (3, 18), both immunological diseases characterized by an increased Th1-mediated inflammatory state. Whether or not IL-10 can ameliorate the hypertension, endothelial dysfunction, and proteinuria seen in PE remains unknown.We (15,22,34,35) have reported previously an experimental model of PE in which pregnant rats treated with low concentrations of DOCA and 0.9% saline exhibit hypertension, proteinuria, endothelial dysfunction, and IUGR, whereas nonpregnant rats receiving identical treatment do not. These DOCA/saline-treated rats have increased vascular oxidative stress due to uncoupled nitric oxide synthesis and elevated Address for reprint requests and other correspondence: B. M.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, recombinant IL-10 has been used with moderate success for the treatment of psoriasis and rheumatoid arthritis (3, 18), both immunological diseases characterized by an increased Th1-mediated inflammatory state. Whether or not IL-10 can ameliorate the hypertension, endothelial dysfunction, and proteinuria seen in PE remains unknown.We (15,22,34,35) have reported previously an experimental model of PE in which pregnant rats treated with low concentrations of DOCA and 0.9% saline exhibit hypertension, proteinuria, endothelial dysfunction, and IUGR, whereas nonpregnant rats receiving identical treatment do not. These DOCA/saline-treated rats have increased vascular oxidative stress due to uncoupled nitric oxide synthesis and elevated Address for reprint requests and other correspondence: B. M.…”
mentioning
confidence: 99%
“…These DOCA/saline-treated rats have increased vascular oxidative stress due to uncoupled nitric oxide synthesis and elevated levels of the proinflammatory cytokines/chemokines IL-2, IL-12, IFN␥, and RANTES (22,34). Furthermore, we (34) reported that excessive maternal immune responses play a major role in the development of PE-like symptoms in these rats as immunosuppression with either azathioprine or mycophenolate mofetil normalized systolic blood pressure, endothelial function, urinary protein excretion, and cytokine profiles.…”
mentioning
confidence: 99%
“…• О 2 -неспряженою eNOS [11][12][13][14][15], а не лише, як раніше вважалося, його надходженням з таких джерел, як мітохондрії [16] , НАДФН-оксидаза [17][18][19], ксантиноксидаза [20] чи ліпо-та циклооксигенази [21].…”
Section: вступunclassified
“…Він може утворюватися за допомогою de novo синтезу індуцибельною NO-синтазою (іNOS), внас-лідок реутилізації стабільних метаболітів NO нітрат-і нітрит-аніонів відповідними редуктазами чи декомпозиції нітрозотіолів, що є депо NO, в судинній стінці [7][8][9][10]. Серед механізмів виникнення оксидативного стресу крім зниження активності ферментів антиоксидантної системи та сполук, що ней-тралізують вільні радикали, перевага остан-нім часом надається збільшенню генерації• О 2 -неспряженою eNOS [11][12][13][14][15] …”
unclassified
“…Additionally, MBG inhibits the proliferation and migration of both cytotrophoblast and CHO cells [21] further interfering with the maturation process ( Figure 6). Finally, rats in which PE had been produced by the administration of DOCA and the replacement of tap water with saline as drinking water, demonstrated increased superoxide production by NADPH oxidase, superoxide degradation of BH4 and uncoupled eNOS which contributed to endothelial dysfunction [22].…”
Section: Other Hypertensive Statesmentioning
confidence: 99%